BDNF influences neural cue-reactivity to food stimuli and food craving in obesity - Bumb, Jan Malte; Bach, Patrick; Grosshans, Martin; Wagner, Xenija; Koopmann, Anne; Vollstädt-Klein, Sabine; Schuster, Rilana; Wiedemann, Klaus; Kiefer, Falk (European archives of psychiatry and clinical neuroscience, 2021)
There is increasing evidence that brain-derived neurotrophic factor (BDNF) impacts on the development of obesity. We are the first to test the hypothesis that BDNF levels might be associated with neural reactivity to food cues in patients suffering from obesity and healthy controls. We assessed visual food cue-induced neural response in 19 obese patients and 20 matched controls using functional magnetic resonance imaging and analyzed the associations between BDNF levels, food cue-reactivity and food craving. Whole-brain analysis in both groups revealed that food cues elicited higher neural activation in clusters of mesolimbic brain areas including the insula (food > neutral). Patients suffering from obesity showed a significant positive correlation between plasma BDNF levels and visual food cue-reactivity in the bilateral insulae. In addition, patients suffering from obesity with positive food cue-induced insula activation also reported significantly higher food craving than those with low cue-reactivity—an effect that was absent in normal weight participants. The present findings implicate that BDNF levels in patients suffering from obesity might be involved in food craving and obesity in humans. This highlights the importance to consider BDNF pathways when investigating obesity and obesity treatment.